From Custom to Modernisation: A Legal-Historical Study of Saudi Arabia's Legal Development - Hajed A. Alotaibi; Bandar A. Alyahya; Saud H. Alharthi (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2026)
Saudi Arabia’s legal system has undergone radical reform, in which the decentralised tribal tradition (ʿurf) and Hanbali jurisprudence (fiqh) have been superseded by a new, modern, codified, and institutionally differentiated legal system. Whatever this change, the processes and reasoning that lead to it are not fully discussed in comparative Islamic law literature. This article presents the strategy of the Saudi state towards a conflict between Islamic normative legitimacy and the administrative demands of modern rule in three historical phases: pre-modern custom and fiqh, early state formation, and the codification of the modern one (2007-2024). The research critically examines primary legal texts and comparative legal scholarship in the Gulf and other jurisdictions with majority-Muslim components of their legal systems, adopting an interpretive, doctrinal-historical, and socio-legal viewpoint. The findings suggest that Saudi legal development exhibits a distinctive state-oriented reconfiguration of doctrines, in which statutory frameworks preserve classical fiqh principles without being overrun by them, yet are predicated on the need for rentier autonomy, the management of legitimacies, and economic integration. This amalgamation is much dissimilar to the modernisation of the law approaches in Egypt, the UAE and Malaysia. Further studies are needed to empirically analyse the implementation of codified statutes in practice by those trained in classical fiqh, and to assess the extent of doctrinal consistency in the newly specialised courts of Saudi Arabia.Keywords: Saudi Arabia; sharia; codification; basic law.